Subtitling multilingual films and multimodal pragmatics : Isle of Dogs as a case study - Wang, Mu Xin (2019)
Multilingual films contain linguistic and paralingustic features, where the latter includes various semiotic modes and constraints which significantly affect the meaning conveyed by subtitle translations. It is challenging for novice translators to be able to interpret such multimodal messages as there is a dearth of research materials and models for analysing multimodal texts. The currently available researches are more focused on source texts which are purely words. It gets even more challenging when filmmakers produce multilingual films that involve non-subtitled foreign language dialogue. As such, a new model for multimodal analysis for subtitle translation needs to be developed. This paper seeks to develop a new multimodal model by adapting certain current models of multimodal transcription, semiotics and pragmatics (collectively “Theories”) for subtitle translation analysis. This paper starts by reviewing the current state of the Theories and explains how adaption of the current models with the resulting new model can improve subtitle translation analysis, which includes the addresssing of potential subtitling constraints a translator may face in the context of multilingual films where only one language is subtitled. In this research, a case study approach is adopted using the Chinese subtitled version of Wes Anderson’s film Isle of Dogs as the subject. The quantitative analysis of the corpus was contrasted with online reviews of the subject which showed that omissions of subtitles for films of such genre should be carefully considered in order to achieve the optimal watching experience. Besides the subtitling field, the new model has the potential for use in research in other disciplines, such as art and literature, with words and image complimenting each other.